Figurative Language Analysis in Billie Eilish’s Selected Songs - Ni Wayan Suastini; Desak Putu Eka Pratiwi; Evantri Ngailo (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
In this study, the varieties of metaphorical language and their significance will be identified and analyzed in the lyrics of a few of Billie Eilish's songs. In this study, two theories were employed. The first is Leech's (1981) theory of meaning, which examines the meaning of figurative language, and the second is Knickerbocker and Reninger's (1974) theory of figurative language. This study employed a qualitative methodology. In this study, simile, metaphor, and hyperbole were discovered to be three types of figurative language employed in a few of Billie Eilish's songs. By listening to the song's lyrics, data was gathered. This research led to the discovery of six different forms of figurative language in song lyrics for the study. They consist of 2 items, or 33% similes, 3 items, or 50% metaphors, and 1 item, or 16% hyperbole. There were 13 items or 48% hyperbola, 4 items or 14% simile, 6 items or 22% metaphor, 2 items or 7% personification, and 1 item each of synecdoche and metonymy. Hyperbole, which accounts for 48% of all figures of speech in these songs, is the most prevalent variety. Two of the seven categories of meaning employed in the lyrics—connotative meaning and emotive meaning—are used to interpret the figurative language.